Knight's castle - Eager, Edward; Bodecker, N. M. (San Diego, Calif. : Harcourt Brace, 1956)
Four cousins, Roger, Ann, Eliza, and Jack, have an extraordinary summer when, after an old toy soldier comes to life, they find themselves transported back to the days of Robin Hood and Ivanhoe.
"An Odyssey/Harcourt Brace young classic."
Sequel: The time garden.
G6
Keywords: Magic -- Fiction; Space and time -- Fiction; Cousins -- Fiction; Knights and knighthood -- Fiction